Amperometric Determination of Dopamine on a Glassy Carbon Electrode Chemically Modified with Cobalt Pentacyanonitrosylferrate - REZAZADEH BARI, MAHMOUD; EMAMALI SABZI, REZA (Asian Journal of Chemistry, 2010)
A cobalt pentacyanonitrosylferrate modified glassy carbon electrode (GC/CoPCNF) was prepared by electrochemical method. The prepared GC/CoPCNF electrode was showed a reversible peak with formal potential of 0.52 V vs. SCE in 0.25 M KNO3 with 50 mVs-1 scans rate. The electrochemical behaviour and stability of the modified electrode were studied by cyclic voltammetry. The experimental results were showed that the GC/CoPCNF electrode is stable within a pH range of 2-8. The modified electrode was exhibited good electrocatalytic activity toward oxidation of dopamine. The effect of pH and applied potential on the electrocatalytic activity of the modified electrode investigated. According to the experimental results the best potential for the amperometric determination of dopamine was 0.70 V vs. SCE. The calibration plot was linear from 10 μM up to 110 μM (r = 0.993) with a good response time (10 s). The detection limit of modified electrode as an amperometric sensor is 8 μM.